Natural radioactivity concentrations of 226Ra, 232Th, and 40K in commercial building materials and their lifetime cancer risk assessment in dwellers - M, Omeje; O. Olusegun, Adewoyin; S. Joel, Emmanuel; C. O., Ehi-Eromosele; PraiseGod, Emenike C.; M. R, Usikalu .; Sayo A., Akinwumi; E., Zaidi; Saeed, Mohammad A. (Taylor & Francis, 2018)
Elevated radioactivity levels of 226Ra, 232Th, and 40K in building materials were measured using gamma-ray spectrometry and their associated lifetime cancer risks were also determined. The mean activity concentrations of 226Ra, 232Th, and 40K are 45.72 § 0.55, 65.90 § 8.89, and 487.32 § 15.20 Bq kg¡1 , respectively. Statistically, the principal component (PC) analysis indicates that higher loadings were recorded in Principal Component One (PC1) with large contribution from 232Th and 40K. The leverage studies indicate that BN Ceramics (BNC) contributes more to the loadings in PC1 followed by Golden Crown Ceramic (GCC) sample and GC. The mean values of 0.399 mSv y¡1 for annual effective dose from the samples surpassed the world’s average value of 0.07 mSv y¡1 by a factor of 5.7. The mean gamma index from the measured samples is 0.644, whereas a mean value of 0.271 for alpha index is noted in the samples. The activity utilization index (AUI) from the samples satisfied the AUI <2, which corresponded with the annual effective dose of <0.3 mSv y¡1 , except interlock Site 2 and Gomez Spain tiles. Significantly, the mean value of excess lifetime cancer risk of 0.0014 is slightly lower than the world average value of 0.29 £ 10¡3